2011
DOI: 10.1007/s13193-011-0086-2
|View full text |Cite
|
Sign up to set email alerts
|

Mastectomy and Contralateral Prophylactic Mastectomy Rates: An Institutional Review

Abstract: Background. Breast conservation surgery (BCS) followed by radiation is as effective as mastectomy for long-term survival and is considered standard of care for early-stage breast cancer. An increasing number of patients are opting for cancer-side mastectomies (CM) and often contralateral prophylactic mastectomies (CPM). Our study investigates if there are increasing trends in our patient population toward CM and CPM and identifies common factors associated with those electing to have more extensive surgery. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Some have hypothesized that women diagnosed at a young age are choosing mastectomy owing to fear of recurrence; the increasing rates of contralateral prophylactic mastectomy in the young age group seems to support this. [53][54][55] Alternatively, women of older age may choose mastectomy for a more expedient treatment, avoiding 6 weeks of radiation, and place less value on the cosmetic outcome as age increases. Another mechanism to explain the influence of age on treatment choice may be to view it as a moderator in the decision-making process for breast cancer instead of the being the main influence underlying treatment choice.…”
Section: Discussionmentioning
confidence: 99%
“…Some have hypothesized that women diagnosed at a young age are choosing mastectomy owing to fear of recurrence; the increasing rates of contralateral prophylactic mastectomy in the young age group seems to support this. [53][54][55] Alternatively, women of older age may choose mastectomy for a more expedient treatment, avoiding 6 weeks of radiation, and place less value on the cosmetic outcome as age increases. Another mechanism to explain the influence of age on treatment choice may be to view it as a moderator in the decision-making process for breast cancer instead of the being the main influence underlying treatment choice.…”
Section: Discussionmentioning
confidence: 99%
“…IntroductIon: Increasing use of bilateral mastectomies for treatment and prevention of breast cancer has generated an increased demand for bilateral breast reconstruction (1)(2)(3)(4). This study analyzes changing patterns of reconstructive methods aimed at meeting the combined goals of increased bilateral reconstruction and decreased morbidity.…”
mentioning
confidence: 99%
“…The incidence of postmastectomy breast reconstruction has been increasing on an annual basis. 1,2 In 2012, the American Society of Plastic Surgeons reported that more than 90,000 of patients in the United States underwent a postmastectomy breast reconstructive procedure. Approximately 80% of the time, a prosthetic breast implant was chosen over an autologous flap reconstruction.…”
Section: Infect Control Hosp Epidemiol 2014;35(1):75-81mentioning
confidence: 99%